Anthropomorphic Robotic Arm Design and Control System using Camera Sensor - Jana Utama (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2017)
In this research will describes about robotic hand anthropomorphic design and control based on the camera. This robotic hand will follow human hand movement with histogram feature, i.e. mean value. Fuzzy logic system is used here because non-linier value. Non-linier value is caused by light intensity and human hand distance with a camera. The movement of robotic hand is limited with just two movements, i.e. flexion and extension. This robotic hand will controlled serially based LabVIEW. This robotic hand is designed with five fingers that moved with servomotor. Each finger has three joints like a human finger, except a thumb which has only two joints. These servo motor will controlled with pulse width modulation (PWM) technique. Based on the testing result, this robotic hand could move following human hand movement with two different light intensity background, i.e. dim backlight and bright backlight. In dim backlight, mean value that read is 15.2 to 20.4,and in bright backlight, mean value that read is 41 to 61.4. The distance testing is also did here. Based on the testing result, this robotic hand could be controlled in 25 cm (minimum distance human hand could be full seen in the camera) to 60 cm, if distance between human hand and camera is more than 60 cm,this robotic hand could not be controlled. This robotic hand also could grip small and medium things finelywith 0.5 cm - 6 cm diameter size, like screwdriver, pen and attractor, but not good enough to grip big thingswith diameter size more than 6 cm, like bottle and cup.